"Can You Search for Me?": Understanding and Improving User‐System Dialogues for Complex Search Tasks. Issue 1 (13th October 2021) - Ghosh, Souvick
Abstract: Most voice‐based personal assistants are suitable for simple tasks which are not conversational but single‐turn question‐answering. To address this limitation, we investigate the dialogue capabilities of commercial conversational systems and compare them to the standards expected by the users. We designed a set of moderately complex search tasks and used two popular personal assistants to evaluate the user‐system interaction. A laboratory‐based user study was conducted with twenty‐five users and seventy‐five search sessions to collect user‐system conversational dialogues (for three search tasks). Next, we show that using a set of simple rules, which could be implemented in the immediate future, it is possible to improve the users' interaction experience and make the system more anthropomorphic. Using a conceptual prototype where a human (Wizard) played the role of the system (unknowing to the users), we demonstrate the efficacy of the guidelines and provide design recommendations for future conversational search systems.